Topical antifungal treatment prevents recurrence of toenail onychomycosis following cure. Issue 5 (30th August 2017) - Shemer, Avner; Gupta, Aditya K.; Kamshov, Adaia; Babaev, Meir; Farhi, Renata; Daniel, C. Ralph; Foley, Kelly A.
Abstract: Recurrence rates are high for onychomycosis, with prophylactic topical antifungal use proposed to counter recurrence. Although this is a reasonable action for many clinicians, few studies have been conducted on the efficacy of topical prophylaxis. A retrospective chart review (2010–2015) was conducted in patients receiving oral terbinafine or itraconazole for toenail onychomycosis. Following complete cure, a topical antifungal (amorolfine, bifonazole, ciclopirox olamine, or terbinafine spray) was used weekly as prophylaxis. Recurrence was recorded along with patient characteristics including demographics and concomitant medical conditions. Data from 320 patients were collected. Recurrence was significantly lower in patients receiving topical antifungal prophylaxis than in no prophylactic treatment following oral terbinafine ( p < .001), but not itraconazole ( p = .185). Regardless of oral treatment, the use of topical antifungals as prophylaxis ( p < .001) decreased, and the number of affected toenails ( p = .048) and family history of fungal infections ( p < .001) increased the likelihood that recurrence would occur. This study supports the use of topical antifungal medications as prophylactic treatment to help prevent recurrence of toenail onychomycosis and suggests that those with a family history of fungal infections should be closely monitored.